Three new species of Stactobiinae (Trichoptera: Hydroptilidae) with the first record of Orinocotrichia Harris, Flint & Holzenthal from Brazil - Souza, Wagner Rafael M. De; Santos, Allan Paulo Moreira; Takiya, Daniela Maeda (Zootaxa, 2016)
Approximately 300 species are assigned to Stactobiinae, most of them occurring in the Old World. Seven species have been recorded from Brazil, six of Flintiella and one of Bredinia. Herein, three new species are described and illustrated based on specimens collected in Maranhão and Piauí states from Northeastern Region of Brazil: Orinocotrichia angelus sp. nov. (Holotype male deposited in CZMA: Maranhão State) can be distinguished by the subgenital plate conspicuous, mesally divided; Flintiella pallida sp. nov. (Holotype male deposited in CZMA: Maranhão State), differs from its cogeners by the process of the subgenital plate; and F. harrisi sp. nov. (Holotype male deposited in CZMA: Piauí State), recognized by the short process of the phallus. The new species of Orinocotrichia is the third species described in this genus and represents the first record of Orinocotrichia from Brazil. Orinocotrichia angelus sp. nov. and F. pallida sp. nov. are the first microcaddisflies species described from Maranhão State, Brazil.